A Content Analysis #pecatluhut on The Political Ethics of Government in Indonesia - Asriadi, Asriadi; Sundari, Cici; Qodir, Zuly (Faculty of Social and Political Science, Universitas Muhammadiyah Tangerang, 2023)
This study analyzes public sentiment regarding Luhut Binsar Panjaitan's PCR test pricing policy, using the hashtag #Pecatluhut on Twitter as the primary data source. The research focuses on the period from November 1 to November 10, 2021, and employs Nvivo 12 Plus software for qualitative data analysis. The study reveals significant negative sentiment towards Panjaitan's policy. Specifically, 45.69% of tweets are categorized as moderately negative, while 15.05% are very negative. Conversely, 38.31% are moderately positive and only 0.94% are very positive. The predominant negative sentiment, with a 45% majority in the moderately negative category, indicates substantial public dissatisfaction. The hashtag #Pecatluhut is characterized by numerous instances of public criticism, reflecting widespread disappointment and lack of respect for Panjaitan’s PCR pricing decisions. The analysis also identifies the most frequently used words in the tweets, underscoring the prevalent themes of criticism and discontent regarding the minister’s policies. This research contributes valuable insights into the impact of health policy decisions on public opinion, emphasizing the critical role of social media in shaping and reflecting public sentiment. The findings are particularly relevant in the context of global discussions on health policy transparency and accountability, highlighting the need for policymakers to engage with public feedback and address concerns proactively.Keywords: Trending topic, Twitter, #Pecatluhut, political ethics ABSTRAKStudi ini menganalisis sentimen publik terkait kebijakan harga tes PCR oleh Luhut Binsar Panjaitan, dengan menggunakan tagar #Pecatluhut di Twitter sebagai sumber data utama. Penelitian ini berfokus pada periode 1 hingga 10 November 2021 dan menggunakan perangkat lunak Nvivo 12 Plus untuk analisis data kualitatif. Studi ini mengungkapkan sentimen negatif yang signifikan terhadap kebijakan Panjaitan. Secara khusus, 45,69% tweet dikategorikan sebagai agak negatif, sementara 15,05% sangat negatif. Sebaliknya, 38,31% bersifat agak positif dan hanya 0,94% yang sangat positif. Dominasi sentimen negatif, dengan mayoritas 45% dalam kategori agak negatif, menunjukkan ketidakpuasan publik yang substansial. Tagar #Pecatluhut ditandai dengan banyaknya kritik publik, mencerminkan kekecewaan luas dan kurangnya rasa hormat terhadap keputusan harga PCR oleh Panjaitan. Analisis ini juga mengidentifikasi kata-kata yang paling sering digunakan dalam tweet, yang menekankan tema utama kritik dan ketidakpuasan terhadap kebijakan menteri. Penelitian ini memberikan wawasan berharga tentang dampak keputusan kebijakan kesehatan terhadap opini publik, menekankan peran penting media sosial dalam membentuk dan mencerminkan sentimen publik. Temuan ini sangat relevan dalam konteks diskusi global mengenai transparansi dan akuntabilitas kebijakan kesehatan, sekaligus menyoroti pentingnya para pembuat kebijakan untuk berinteraksi dengan umpan balik publik dan secara proaktif menangani kekhawatiran masyarakat.Kata Kunci: Trending topic, Twitter, #Pecatluhut, etika politik